Is the Use of Cardioactive Steroids Appropriate in Managing Aluminium Phosphide Poisoning-Induced Heart Failure? - Marashi, Sayed Mahdi; Majidi, Mohammad; Sadeghian, Mehran; Ahmadi, Shapour; Raji Asadabadi, Hojatollah; Nasri Nasrabadi, Zeynab (Arhiv za higijenu rada i toksikologiju, 2013)
Following the publication of a review on aluminium phosphide poisoning in your journal, as well as another letter to the editor regarding this subject, we would like to add to this discussion (1,2). Patients with acute aluminium phosphide poisoning generally suffer from multiple organ dysfunction due to diminished mitochondrial activity and oxidative phophorylation. This is the result of the direct effect of toxins on mitochondrial performance (3,4). As Shadnia et al. (5) stated, this toxicity may, among other consequences, lead to congestive heart failure. Cardioactive steroids were until recently considered as a supposition that improves cardiac functioning and were used in the treatment of heart failure (6).